The Formulation of Kepok Banana Flour (Musa paradisiaca Linn) in Muffin Processing as an Alternative to Supplementary Feeding for School Children - Maryam Razak; Shofi Hikmawatisisti; I Komang Suwita (Media Gizi Pangan, 2022)
ABSTRACT Background: Nutritional problems in elementary school children are still quite high. Based on the Riskesdas (2018), the prevalence of underweight was 9.2% (BMI/U) in school children aged 5-12 years. Malnutrition occurs due to lack of intake of food sources of energy and protein, if it occurs in school-age children, it can inhibit growth, reduce intelligence levels and become susceptible to infectious diseases. Objective: To determine the effect of the formulation of kepok banana flour on muffin processing as an alternative supplementary feeding for school children on proximate levels (water content, ash content, protein, fat, carbohydrates, energy) and organoleptic quality. Method: This type of research is experimental. Completely Randomized Design (CRD) using 4 levels of treatment with the proportions of wheat flour: banana kepok flour, are P0 (100: 0), P1 (60: 40), P2 (50: 50), and P3 (40: 60). treatment based on the PMT-AS (2016) program, are 300 calories of energy, 6 grams of protein, 13 grams of fat, and 40 grams of carbohydrates. Results: The results showed that the formulation of banana flour and soy milk on muffins had a significant effect (p<0.05) on ash, protein, and fat content, but did not have a significant effect (p>0.05) on water content, carbohydrates, and energy values.The panelists preference for color and taste had a significant effect (p<0.05 ), but had no significant effect (p>0.05) on aroma and texture. The best treatment of muffins at P1 (60:40). It is necessary to add cocoa powder to cover the aftertaste and unpleasant taste of the muffin. Key words : PMT-AS, banana flour muffin, proximate content, organoleptic quality